UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR PAIBP TENTANG QODHO’ DAN QODAR DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - sunarto sunarto (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Abstract Qodo and Qodar is the last pillar of faith or the sixth. Qodo and Qodar concepts are similar, but quietly different, so that the students so confuse and have learning difficulties. The purpose of this research is to analyze the enhancement of the VI B students of Public Elementary School 1 Kunduran learning outcomes of Islamic Education and Character about Qodo and Qodar through Cooperative Learning with Jigsaw type on the Second Semester of 2019/2020 Academic Year. This is a Classroom Action Research (CAR). The action is Cooperative Learning with Jigsaw type or Jigsaw Method. The place of this research is on the VI B Class of Public Elementary School 1 Kunduran. The time of this research is the early period on the Second Semester of 2019/2020 Academic Year. The subjects are 14 students, consists of 9 boys and 5 girls. Techniques of collecting data are nontest and test. Tools of collecting data are observation sheet, camera application and test with written question. Technique of analyzing data is comparative-descriptive. The procedure is Kemmis and McTaggart Model. The result is learning outcomes enhanced from unsatisfactory category to satisfying. Keywords: Learning Outcomes, Islamic Education and Character, Qodo’ and Qodar, Cooperative Learning, Jigsaw